Reactivating the agrarian reform - Tobón, Alonso (La Sociología en sus Escenarios, 2009)
Abstract. After evaluating the 70s Agrarian Reform in Colombia, it could be easily found how its purposes of improving the redistribution of the land and diminishing the tremendous concentration of the land had miserably failed (Tobón:1971). Reasons for such a failure could not be explained neither in terms of a deceit led by the dominant classes nor as a malicious falsification organized by the governments. Rather it ought to have been analyzed as part of a same logic under which operates the system. To achieve this, the system must not have been understood as an enclosed thing, but as making part of the wider system of capitalist domination. Resumen. Al hacer la evaluación de la reforma agraria en Colombia de los años 70s, se pudo apreciar como sus propósitos para mejorar la redistribución de la tierra y disminuir la concentración escandalosa de la tierra, habían fracasado en forma miserable. (Tobón: 1971). Las razones de semejante fracaso no podían ser explicadas en términos de un engaño que las clases dominantes o como una falsificación maligna organizada por los gobiernos, sino más bien tenían que ser analizadas como parte de la lógica misma de cómo opera el sistema. Para lograr esto, el sistema no tenía que ser entendido como una cosa encerrada en sí sino haciendo parte del sistema más amplio de dominación del modo de producción capitalista.